Late presentation of a Type IV sacrococcygeal teratoma in a 16-year-old female: A case report - Ahmed Eldeib; Carlos A. Reck; Koby Herman; Emily Yang; Stefani Manis; Francisca Velcek (Journal of Pediatric Surgery Case Reports)
Introduction: Sacrococcygeal teratomas (SCTs) are rare germ cell tumors, predominantly diagnosed in neonates. These tumors are categorized as mature, immature, or malignant, with mature teratomas posing a lower risk for malignant transformation. While symptoms commonly arise from the mass effect, late presentation in adolescents or adults is rare. Case presentation: A 16-year-old female with no significant past medical or surgical history presented with perianal pain, constipation, and fever. On physical exam, the rectum was collapsed by a mass. The laboratory work-up showed leukocytosis and an elevated C-reactive protein. Lactate dehydrogenase (LDH), alpha-fetoprotein (AFP), and beta-human chorionic gonadotropin (β-HCG) levels were within normal limits. A CT scan of the abdomen and pelvis revealed a 12 x 16 × 16 cm complex mass in the presacral region. Further evaluation with a pelvic MRI confirmed the presence of a multiloculated mass with mixed solid and cystic components, rim enhancement, and possible coccygeal involvement suggestive of a sacrococcygeal teratoma. Given the size and location of the mass, we decided for a combined abdomino-perineo-sacral surgical approach. The patient received Ceftriaxone and Metronidazole before the operation. We started with a midline laparotomy and detached the tumor from the intra-abdominal structures, and we continued with a posterior sagittal approach. The tumor appearance was consistent with a mature teratoma and had purulent fluid within the cystic component. We removed the mass completely and did a coccygectomy. The postoperative course was complicated by a retroperitoneal collection and a posterior wound dehiscence that required several washouts, debridement, vacuum-assisted closure therapy, and a long course of antibiotics. She was discharged home on postoperative day 32. She is being followed with yearly MRIs. Conclusion: Superinfection of mature teratomas can lead to postoperative infectious complications. Pre-operative and postoperative antibiotics are recommended when resecting mature teratomas.